Setting the Edge: How the NCAA Can Defend Amateurism by Allowing Third-Party Compensation - Feiner, Benjamin (The Columbia Journal of Law & the Arts, 2020)
Part I of this Note describes the NCAA’s formation and its contemporary model. It also discusses the antitrust and labor law challenges the NCAA has faced in litigation over its existing approach. Part II explores the twin challenges posed by the Fair Pay to Play Act, which cannot be sufficiently addressed through a unilateral NCAA response. The first challenge is the inconsistency in state laws, which undermines any NCAA response that seeks to impose a uniform set of rules across the country. The second is that the Fair Pay to Play Act fails to address existing legal challenges to the NCAA’s amateur model. Therefore, even if the NCAA accepts a change in the status quo, it misses an opportunity to address the increasingly uncertain broader legal status of its restrictions on college athlete compensation. In response to these challenges, Part III contends that the NCAA should more urgently pursue a comprehensive federal legislative compromise that sacrifices restrictions on NIL compensation in return for statutory protections from further labor and antitrust litigation. This type of federal legislation would have the additional benefit of preempting state laws on the subject, thus maintaining a uniform system of rules. By losing the battle to win the war, the NCAA will be well positioned for continued viability in the coming decades